2019
DOI: 10.9734/jammr/2019/v31i230283
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Single Agent Rectal Diclofenac versus a Combination of Rectal Diclofenac and Intramuscular Pentazocine, on Post Caesarean Section Pain Relief in a Tertiary Institution in Southern Nigeria

Abstract: Background: Caesarean section commonly causes moderate to severe pain in the first 24 hours after surgery with associated discomfort, delayed ambulation, difficulty initiating breastfeeding and prolonged hospital stay. Receiving adequate analgesia after caesarean section is very important for the patient’s comfort, overall wellbeing and recovery. Objective: To compare the efficacy, time to rescue-analgesia and side effects of single agent rectal diclofenac versus its combination with intramuscular pentaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…This showed that that the socio-demographic variables were evenly distributed between the two groups and this eliminated any possible confounding influence from them. This was similar to reviewed studies with similar drug combination [20,22,51,52] .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This showed that that the socio-demographic variables were evenly distributed between the two groups and this eliminated any possible confounding influence from them. This was similar to reviewed studies with similar drug combination [20,22,51,52] .…”
Section: Discussionsupporting
confidence: 86%
“…This is similar to study by Adeniji et al [20] who noted that the use of PP or TP had better satisfaction that pentazocin or tramadol alone. Also, both Kwosah et al [52] and Egede et al [51] recorded good maternal satisfaction when bimodal agents were used compared to unimodal agent as was seen in our study were we used bimodal agents, though both unimodal agents and pentazocine were not considered in our study. However, Mitra et al [22] did not study the level of maternal satisfaction and this was one of the gaps noted justifying the reason for our study.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…12,13 These current findings were similar to those of previous reports that suggested that the use of multimodal analgesia gives better pain relief than unimodal analgesia. 29,30 It should be noted that the level of pain perception in the first hour after surgery was not significantly different between the two groups. This could be due to the variable duration of spinal anaesthesia that was used in the patients, the varying length of time used to complete the surgery and the fixed time in which the drugs were commenced on both groups (1 h after surgery), However, after commencement of the drugs in both groups, the difference in pain perception became significantly between the two groups.…”
Section: Discussionmentioning
confidence: 84%